Offline versus Online Learning - Jaka Satria Warman; Utari Akhir Gusti (Bioeducation Journal, 2021)
While there have been numerous studies focusing on finding students' perception on online learning, the studies regarding the perception on both online and offline learning have generally been overlooked. This study, therefore, attempted to fill this void. The main objective is to find out whether offline learning is more preferable than online learning. This descriptive research employed questionnaire with Likert scale through online google forms in collecting the data. 36 students from Biology Department, Universitas Negeri Padang participated in this research. The respondents were asked some questions regarding learning implementation, lecturer's competency and facilities to know their perception. The research found that the students generally showed more positive attitude towards offline learning which can be perceived from the comparison of percentagesin each question. The findings then suggest that students preferred offline learning to online learning and hence, offline learning is more recommended to be conducted.